Localize lesion of horner’s syndrome based on anhydrotic pattern - Basri, Muhammad I.; Wardani, Emy; Basir, Hasmawaty; Wuysang, Audry D. (Hasanuddin University, 2019)
Objective: The current case series will discuss about two horner syndrome cases with a different pattern of anhydrotic.Methods:Male 54 years old came with punctured and burned pain sensation at left hand for the last one year which radiated along the shoulder toward the tip of left fingers. There were 10 kgs of weight loss. Neurological examination showed unequal pupil size 2.5mm/1.5mm, left ptosis, left hemifacial and left arm anhidrosis. Cervical MRI showed burstfracture involved CV T1 pedicle.Results: CaseIMSCT Thorax showed suspicious of neurogenic tumor which resulted in CV T1 destructionandcaseIIMSCT thorax showed left lung collapse due to pleural effusionConclusion: Anhidrotic pattern will be an essential factor in making a topical diagnosis for patients with Horner syndrome, which also can be a fundamental basis in choosing the next additional examinations required to find the etiology.Keywords:Anhidrotic pattern, Horner’s syndrome, Sympathetic nerve